Study on Topology Optimization Design for Additive Manufacturing - Anh, Nguyen Thi; Quynh, Nguyen Xuan; Tung, Tran Thanh (Engineering, Technology & Applied Science Research, 2024)
Topology optimization is an advanced technique for structural optimization that aims to achieve an optimally efficient structure by redistribution materials while ensuring fulfillment of load-carrying, performance, and initial boundary. One of the obstacles in the process of optimizing structures for mechanical parts is that these optimized structures sometimes encounter difficulties during the manufacturing process. Additive Manufacturing (AM), also known as 3D printing technology, is a method of manufacturing machine parts through joining layers of material. AM opens up the possibility of fabricating complex structures, especially for structures that have been subjected to topology optimization techniques. This project aims to compare the initial shape of a box under static load and its shape after optimization. The subsequent produced models have reduced weights of 43%, 59%, 70%, 73%, and 77%, respectively, weighing 491.45 g, 357.42 g, 261.31 g, 235.56 g, and 203.87 g. All models are capable of supporting a 10 kg load, demonstrating the ability of the structure to meet technical specifications. The results show that combining structural optimization and additive manufacturing can take advantage of both approaches and show significant potential for modern manufacturing.